Aqueous slurry of coating coloring composition for paper, board, etc.

By using anionic lignin-carbohydrate composite as a dispersant in the aqueous slurry, the problem of insufficient stability and processability of aqueous slurry in the prior art is solved, and high efficiency is achieved for the manufacture of paper, board, etc. Alternative paint coloring compositions.

CN116057230BActive Publication Date: 2025-02-07KEMIRA OY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202180057431.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-09-18
Filing Date
2021-09-16
Publication Date
2025-02-07
Estimated Expiration
2041-09-16

AI Technical Summary

Technical Problem

In the prior art, conventional petroleum-based synthetic polymer dispersants in aqueous slurries used for production of paper, board, etc. have problems with insufficient stability and processability, and are difficult to replace.

Method used

Anionic lignin-carbohydrate complex is used as the dispersant in the aqueous slurry, and a stable aqueous slurry is formed by covalent binding with inorganic mineral particles.

Benefits of technology

The stability and processability of aqueous slurries are improved, and can effectively replace petroleum-based synthetic polymer dispersants, and are suitable for the manufacture of paint coloring compositions for paper, boards, etc.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004113457170000091
    Figure BDA0004113457170000091
Patent Text Reader

Abstract

The present invention relates to an aqueous slurry of a coating composition for making paper, board, etc., which contains inorganic mineral particles and a dispersant, which is an anionic lignin-carbohydrate complex in which lignin and carbohydrate are covalently bound to each other.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an aqueous slurry for a coating colour composition for paper, board etc. and to the use of anionic lignin-carbohydrate complexes according to the appended independent claims. Background Art

[0002] The aqueous slurry that comprises inorganic mineral particles is widely used in various industries.For example, in the manufacture of paper, board etc., the aqueous slurry that comprises inorganic mineral particles is used to prepare coating coloring composition.Coating coloring composition is applied on the surface of paper, board etc., wherein they especially improve intensity, printability and the outward appearance of paper, board etc.This coating coloring composition is the aqueous slurry based on inorganic mineral particles, wherein added adhesive and possible other additives, such as co-adhesive, preservative, dispersant, defoamer, lubricant, hardener and optical brightener.But the main component of this coating coloring composition is inorganic mineral particles.

[0003] When preparing coating coloring composition, inorganic mineral particles are slurried with water. In order to improve the stability and processability of the aqueous slurry containing inorganic mineral particles, a dispersant is usually added to the aqueous phase of the slurry. The dispersant improves the high and / or low shear viscosity characteristics of the slurry, for example. The dispersant also ensures the appropriate behavior of the coating coloring composition during the treatment period before its application and during its application on paper, board, etc., for example stability.

[0004] Many dispersants are known. However, many conventional dispersants are synthetic polymers, which are derived from petroleum-based raw materials. In view of the current expectation of increasing the use of materials derived from renewable sources, it is clear that there is an interest in replacing all or part of petroleum-based synthetic polymer dispersants. However, at the same time, the characteristics (such as viscosity and stability) of the aqueous slurry comprising inorganic mineral particles should remain on the same level so that they can be used to manufacture coating coloring compositions intended for paper, board, etc. Summary of the invention

[0005] The object of the present invention is to minimize or possibly even eliminate the disadvantages existing in the prior art.

[0006] It is also an object to provide an aqueous slurry comprising inorganic mineral particles comprising a dispersant obtained from a renewable source.

[0007] Another object of the present invention is also to provide an aqueous slurry containing inorganic mineral particles, which is stable and easy to prepare, and which is suitable for preparing a coating coloring composition for coating of paper, board, etc.

[0008] These objects are achieved by the invention having the following features presented in the characterizing part of the independent claim. Some preferred embodiments are disclosed in the dependent claims.

[0009] Unless explicitly stated otherwise, the features stated in the dependent claims and the embodiments in the description are freely combinable with each other.

[0010] The exemplary embodiments and their advantages presented herein relate to all aspects of the invention by the applicable part, even if not always mentioned individually.

[0011] A typical aqueous slurry of a coating coloring composition for making paper, board, etc. according to the present invention comprises inorganic mineral particles and a dispersant which is an anionic lignin-carbohydrate complex.

[0012] A typical use of the anionic lignin-carbohydrate complex according to the invention is as a dispersant for inorganic mineral particles in aqueous slurries for coating coloring compositions for paper, board and the like.

[0013] It has now been surprisingly found that anionic lignin-carbohydrate complexes (in which lignin and carbohydrates are covalently bound to each other) can be used as dispersants in aqueous slurries containing inorganic mineral particles. Compared to aqueous slurries of inorganic mineral particles using conventional synthetic petroleum-based dispersants, the aqueous slurries thus obtained have at least similar, sometimes even improved properties, such as viscosity and / or stability. The present invention provides the possibility of effectively reducing the use of synthetic petroleum-based dispersant polymers and increasing the use of materials derived from renewable sources. The aqueous slurries thus obtained are particularly suitable for the manufacture of coating coloring compositions for coatings of paper, board, etc.

[0014] Anionic lignin-carbohydrate complexes suitable for the present invention are natural polymer complexes comprising lignin and carbohydrates, preferably hemicellulose, covalently bound to each other. Therefore, lignin-carbohydrate complexes are conjugates of lignin and at least one carbohydrate, which are irreversibly bound to each other in the overall structure. The lignin and carbohydrates of the complex cannot be separated from each other without permanently destroying the structure of the complex. Anionic lignin-carbohydrate complexes may have a branched structure. For example, lignin or carbohydrates may form the main chain structure of the complex, and other components (carbohydrates or lignin) may form side groups covalently bound to the main chain structure.

[0015] The lignin-carbohydrate complex can be formed by lignin and one or more carbohydrates such as hemicellulose. The carbohydrates in the lignin-carbohydrate complex can preferably be formed by monosaccharides such as galactose, glucose, mannose, arabinose and / or xylose. The exact amount of monosaccharides and their relative ratios depend on the wood species, such as hardwood / softwood, which have been used in pulping processes and the lignin-carbohydrate complex is also derived from them. Monosaccharides can be present in the lignin-carbohydrate complex as sugar residues (covalently bound to lignin).

[0016] The lignin-carbohydrate complex may contain different anionic functional groups, such as sulfonate groups, carboxyl groups, phenolic groups and / or any combination thereof. The lignin-carbohydrate complex may contain, for example, sulfonate groups of >1300-1700 μmol / g, preferably 1400-1600 μmol / g; carboxyl groups of 300-500 μmol / g, preferably 350-450 μmol / g; and / or phenolic groups of 125-250 μmol / g, preferably 150-225 μmol / g.

[0017] Lignin-carbohydrate complexes suitable for use in the present invention can be obtained, for example, from a side stream of a pulping process. In one embodiment, suitable lignin-carbohydrate complexes can be obtained by enzymatic treatment of lignin-carbohydrate materials derived from a pulping process. For example, the lignin-carbohydrate complexes can be obtained by separating lignin-carbohydrate materials from a side stream of a wood pulping process by filtration (such as membrane filtration), and preferably treating the separated lignin-carbohydrate materials by enzymatic treatment using laccase. Alternatively, lignin-carbohydrate complexes can be separated from lignocellulosic materials (such as wood or pulp) by using separation and fractionation methods known per se. For example, it is possible to separate lignin-carbohydrate complexes by fractionating lignin from industrial processes (such as kraft pulping or sulfite pulping). Suitable lignin fractionation methods include, for example, solvent fractionation or precipitation fractionation. In solvent fractionation, various organic solvents and binary mixtures thereof can be used, such as acetone-hexane, acetone-water, ethanol-water, propylene glycol monomethyl ether-water. This fractionation method is described in particular in Int. J. Biol. Macromolecules 106 (2018) 979-987.

[0018] According to a preferred embodiment of the present invention, the anionic lignin-carbohydrate complex is an anionic lignin sulfonate-carbohydrate complex. It can be obtained, for example, by membrane filtration from a pre-hydrolyzed mixture of a sulfite pulping process of wood, and thereafter treated by enzymatic oxidation treatment (preferably by laccase). Preferably, the filtered pre-hydrolyzed mixture is obtained from a sulfite pulping process of wood. The pre-hydrolyzed mixture may contain wood-based components and pulping chemicals. Suitable anionic lignin sulfonate-carbohydrate complexes are disclosed in, for example, BioResources 13 (4), 7606-7627, 2018, and they are commercially available from Swedish Ecohelix AB.

[0019] The anionic lignin-carbohydrate complex may have an anionic charge density of less than -0.2 meq / g, preferably less than -0.5 meq / g, more preferably less than -0.85 meq / g, measured at pH 7. The anionic charge density of the complex may be from -0.2 meq / g to -2.5 meq / g, preferably from -0.5 meq / g to -2.4 meq / g, more preferably from -0.85 meq / g to -2.3 meq / g, measured at pH 7. Sometimes, the anionic charge density of the complex may be from -0.5 meq / g to -1.75 meq / g, preferably from -0.85 to -1.5 meq / g, measured at pH 7. The anionic charge density of the complex may even be from -2.0 meq / g to -2.3 meq / g, preferably from -2.1 to -2.2 meq / g, measured at pH 7. All charge density values ​​are given on a dry basis and were measured using a Mütek particle charge detector.

[0020] The lignin-carbohydrate complex may have a weight average molecular weight MW of >3500 g / mol, preferably >4000 g / mol, more preferably >5000 g / mol. The lignin-carbohydrate complex may have a weight average molecular weight MW in the range of 3500-90 000 g / mol, preferably 4 000-80 000 g / mol, more preferably 5000-70 000 g / mol.

[0021] According to one embodiment, the lignin-carbohydrate complex may preferably have a relatively high molecular weight. Without wishing to be bound by theory, it is assumed that the high molecular weight provides at least some of the unexpected effects that have been observed. The lignin-carbohydrate complex may have a weight average molecular weight MW of >8000 g / mol, preferably >10 000 g / mol, more preferably >12000 g / mol or >15 000 g / mol, sometimes even >20 000 g / mol or >25 000 g / mol. The lignin-carbohydrate complex may have a weight average molecular weight MW in the range of 8 000-50 000 g / mol or 10 000-45 000 g / mol, preferably 12000-40 000 g / mol or 15 000-37 000 g / mol. Sometimes, the lignin-carbohydrate complex may have a weight average molecular weight MW in the range of 20 000-45 000 g / mol, preferably 25 000-40 000 g / mol, more preferably 25 000-35 000 g / mol or 25 000-27 000 g / mol. According to one embodiment, the lignin-carbohydrate complex may have a weight average molecular weight MW in the range of 15 000-120 000 g / mol or 20 000-90 000 g / mol, preferably 25000-80 000 g / mol, more preferably 30 000-70 000 g / mol.

[0022] The lignin-carbohydrate complex may comprise lignin and carbohydrates, preferably hemicellulose, in a ratio of from 90:10 to 10:90, preferably from 80:20 to 20:80, more preferably from 75:25 to 25:75 (lignin: carbohydrates). According to one embodiment of the invention, the lignin-carbohydrate complex may comprise at least 10 wt%, preferably at least 15 wt% carbohydrates, preferably hemicellulose, calculated from the total dry weight of the complex. The lignin-carbohydrate complex may comprise carbohydrates in the range of 10-40 wt%, 10-30 wt% or 15-25 wt%, calculated from the total dry weight of the complex.

[0023] According to one embodiment of the present invention, the aqueous slurry comprises 0.01-10pph, preferably 0.05-5pph, more preferably 0.1-3pph of lignin-carbohydrate complexes calculated per 100 parts of inorganic mineral particles. Sometimes, the aqueous slurry may comprise 0.1-3.5pph, preferably 0.25-3.0pph, more preferably 0.5-2.5pph or 1.0-2.0pph of lignin-carbohydrate complexes calculated per 100 parts of inorganic mineral particles. In this article, if not otherwise specified, as conventional in the art, by giving the total value of 100 of inorganic mineral particles, and calculating the amount of other components relative to the total amount of inorganic minerals, the amount of a single component of the composition is given. The ratio of all components is given in dry parts and active agents.

[0024] The aqueous slurry comprising inorganic mineral particles and lignin-carbohydrate complexes according to the present invention is stable. It has been observed that the lignin-carbohydrate complex helps the inorganic mineral particles remain dispersed in the aqueous phase of the aqueous slurry, and therefore no phase separation or viscosity changes in the slurry over time are observed. The unchanged viscosity of the slurry comprising inorganic mineral particles over time is a clear indication of the stability of the aqueous slurry. According to one embodiment, the difference between a first viscosity value measured on the slurry immediately after the preparation of the aqueous slurry and a second viscosity value measured on the aqueous slurry 2 hours after the preparation of the slurry is less than 10%, preferably less than 7.5%, more preferably less than 5%.

[0025] The inorganic mineral particles that can be used in the present invention are those that are commonly used to make coating coloring compositions for coatings such as paper and board. The inorganic mineral particles can be selected from calcium carbonate, kaolin, calcined kaolin, talc, titanium dioxide, gypsum or any mixture thereof. Calcium carbonate can be ground calcium carbonate (GCC) or precipitated calcium carbonate (PCC) or a mixture thereof. Preferably, the inorganic mineral pigment is selected from kaolin, precipitated calcium carbonate, ground calcium carbonate and any mixture thereof. The aqueous slurry can contain one or more inorganic mineral particles of an inorganic mineral with a particle size D50 <5 μm. According to one embodiment, the aqueous slurry contains coating-grade inorganic mineral particles, wherein at least 45% of the inorganic mineral particles have a particle size <2 μm.

[0026] The aqueous slurry containing the inorganic mineral particles can be prepared simply by adding the anionic lignin-carbohydrate complex as a dispersant to the aqueous phase. Then, any suitable inorganic mineral in the form of particles, paste or cake, such as precipitated calcium carbonate or titanium dioxide, is added to the aqueous phase by any suitable means, such as a screw conveyor, and the final aqueous slurry is obtained by mixing the aqueous phase with the inorganic mineral particles.

[0027] The aqueous slurry may have a solids content in the range of 20-80 wt%, preferably 40-70 wt%, more preferably 50-70 wt%.Typically, the aqueous slurry of inorganic mineral particles comprises at least 20 wt% water.

[0028] The aqueous slurry according to the present invention is particularly suitable for coating coloring compositions for coating paper, board, etc. According to one embodiment, the aqueous slurry may have a viscosity of ≤2500 mPas, preferably ≤2000 mPas, measured at 23°C with a Brookfield viscometer, DV-E type, 100 rpm. A suitable spindle is used for this measurement range. The viscosity of the aqueous slurry according to the present invention may be in the range of 500 mPas-2500 mPas, typically 1000 mPas-2000 mPas.

[0029] The aqueous slurry may further comprise at least one thickener. DETAILED DESCRIPTION

[0030] Example 1

[0031] In Example 1, anionic lignin sulfonate-carbohydrate complexes A1, A2 and A3 were tested as dispersants for clay pigment particles (coating grade, minimum of 45% particles less than 2 μm). Lignosulfonate-carbohydrate complexes A1 (DS 7.15 w-%), A2 (DS 10.75 w-%) and A3 (DS 26.1 w-%) were obtained from Ecoheli AB, Sweden. Reference dispersant B was a commercial polyacrylate dispersant (DS 40 w-%, FennoDisp A41, Kemira Oyj).

[0032] The amounts of water and clay mineral used were calculated so that the final slurry had a dry solids content of 72 wt%.

[0033] In the experiment, 100 pph of clay pigment particles were added to water and mixed in a high shear mixer for 15 minutes. The viscosity of the aqueous clay slurry was measured at 23°C using a Brookfield viscometer, model DV-E, at speeds of 100 rpm and 50 rpm, and using a suitable spindle within the measuring range. The dispersant used was added stepwise, 0.025 pph each time. After each addition, the aqueous clay slurry was mixed again for 10 min and the viscosity was measured.

[0034] The viscosity measurements were performed at 0 pph, 0.025 pph, 0.05 pph, 0.075 pph and 0.1 pph of dispersant. As is conventional in the art, the total amount of clay pigment is given a value of 100, and the amounts of other components are calculated relative to the amount of total pigment and given in pph (parts per 100). All components are given as active dry parts.

[0035] The results of Example 1 are shown in Table 1.

[0036] As can be seen from Table 1, anionic lignin sulfonate-carbohydrate complexes A1, A2 and A3 provide aqueous clay slurries with viscosity values ​​similar to commercial dispersants. This indicates that lignin sulfonate-carbohydrate complexes A1, A2 and A3 can be used to fully or partially replace commercial dispersants conventionally used to disperse clay pigments in aqueous slurries.

[0037] The project leading to this application has received funding from the Bio Based Industries Joint Undertake (JU) under Grant Agreement No 837866. JU receives support from the European Union's Horizon 2020 research and innovation programme and the Bio BasedIndustries Consortium.

[0038] Although the invention has been described with reference to what currently appear to be the most practical and preferred embodiments, it should be understood that the invention is not limited to the above-described embodiments, but the invention is intended to cover various modifications and equivalent technical solutions within the scope of the appended claims.

[0039] Table 1 Results of Example 1

[0040]

Claims

1. An aqueous slurry of a coating coloring composition for making paper and board, the slurry comprising inorganic mineral particles and a dispersant, the dispersant being an anionic lignin-carbohydrate complex in which lignin and one or more carbohydrates are covalently bound to each other, the carbohydrates in the anionic lignin-carbohydrate complex being formed by monosaccharides, and the anionic lignin-carbohydrate complex having a weight average molecular weight MW in the range of 8000-50000 g / mol, the anionic lignin-carbohydrate complex having an anionic charge density of less than -0.2 meq / g measured at pH 7, and the anionic lignin-carbohydrate complex comprising at least 10 wt% of carbohydrates calculated on the total dry weight of the complex.

2. The slurry according to claim 1, characterized in that The anionic lignin-carbohydrate complex comprises anionic functional groups selected from sulfonate groups, carboxyl groups and / or phenolic groups.

3. The slurry according to claim 1 or 2, characterized in that The anionic lignin-carbohydrate complex has a weight average molecular weight MW in the range of 10 000-45 000 g / mol.

4. The slurry according to claim 1 or 2, characterized in that: The anionic lignin-carbohydrate complex has an anionic charge density measured at pH 7 ranging from -0.2 meq / g to -2.5 meq / g.

5. The slurry according to claim 1 or 2, characterized in that The anionic lignin-carbohydrate complex has a lignin:carbohydrate ratio of from 90:10 to 10:

90.

6. The slurry according to claim 1 or 2, characterized in that The anionic lignin-carbohydrate complex comprises galactose, glucose, mannose, arabinose and / or xylose residues covalently bound to lignin.

7. The slurry according to claim 1 or 2, characterized in that The slurry has a solid content of 20 to 80 wt %.

8. The slurry according to claim 1 or 2, characterized in that The slurry contains anionic lignin-carbohydrate complexes in an amount of 0.01-10 pph per 100 parts of the inorganic mineral particles.

9. The slurry according to claim 1 or 2, characterized in that The inorganic mineral particles are selected from kaolin, precipitated calcium carbonate, ground calcium carbonate and any mixture thereof.

10. The slurry according to claim 1 or 2, characterized in that The slurry has a o Viscosity ≤ 2500 mPas measured at 400 °C with a Brookfield DV-E, 100 rpm.

11. The slurry according to claim 1 or 2, characterized in that The difference between a first viscosity value measured on the slurry immediately after the slurry is prepared and a second viscosity value measured on the slurry 2 hours later is less than 10%.

12. Use of anionic lignin-carbohydrate complexes in which lignin and one or more carbohydrates are covalently bound to each other as dispersants for inorganic mineral particles in aqueous slurries of coating compositions for making paper and board, wherein the carbohydrates in the anionic lignin-carbohydrate complexes are formed by monosaccharides, and the anionic lignin-carbohydrate complexes have a weight average molecular weight MW in the range of 8000-50000 g / mol, the anionic lignin-carbohydrate complexes have an anionic charge density of less than -0.2 meq / g measured at pH 7, and the anionic lignin-carbohydrate complexes contain at least 10 wt% carbohydrates calculated on the total dry weight of the complexes.

Citation Information

Patent Citations

  • Dispersant

    CN105408011A

  • Alkali-o2 oxidized lignin as dispersant

    CN108350177A